Improving the connectivity of junction-based routing in city scenarios of VANETs. (10th September 2019) - Zahedi, Khalid; Zahedi, Yasser; Ismail, Abdul Samad
In this work, a new protocol exclusively designed for improving the connectivity of junction-based routing in vehicular ad hoc networks (VANETs) has been introduced. Its main characteristic is eliminating the dependency on traffic density during the process of routing paths construction in city environments. In particular, the proposed protocol employs a multi-metric junction selection mechanism to select the optimal next candidate junction. The novelty of the proposed mechanism is its exploitation of RSUs as one of the selection metrics. Results have shown an increase in the packet delivery ratio and a decrease in the end-to-end delay of the proposed protocol compared to other junction-based protocols.